Ograniczenia niezależności w układzie dziennikarz – redaktor naczelny – wydawca (właściciel) w prasie lokalnej - Jurga, Ewa (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2005)
Financial standing of a newspaper is decisive for journalist freedom and independence. It may be observed in the journalistic reality of local newspapers, particularly of those privately owned, that financial matters usually predominate over journalistic ethics. Such practice overshadows the apparently noncommercial nature of the press that is emphasized by the editorial office. Most titles make an overt reference to their independence and stimulating role. The latter is most likely to refer to the influence the press exerts on the public awareness, which contradicts the commercial purposes. In contrast to private newspapers, the titles owned or subsidized by local governments are not profit-oriented. The journalists in such newspapers frequently work pro publico bono and are not remunerated for their work. It is essential for such editorial teams that the society approves the institutions their newspapers represent.